DESKRIPSI MOTIVASI BELAJAR SISWA KELAS XI SMA NEGERI 06PONTIANAK - Sulastri Sulastri; Abas Yusuf; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe background of this research is the problem of achievement motivation which is a problem that deserves attention, because the lack of achievement motivation is not just an indication of a decline in enthusiasm and enthusiasm for learning but can affect the achievement of learning goals. Based on a survey conducted at SMA Negeri 6 Pontianak, there were many students who did not yet have achievement motivation, for example lack of confidence, lack of creativity in actualizing themselves. "What is the achievement motivation of grade XI students of SMA Negeri 6 Pontianak?" The general objective of this study was to determine the achievement motivation of grade XI students of SMA Negeri 6 Pontianak. In this study involving a single variable, achievement motivation.In this study a descriptive method was used. The form of research is a form of survey (survey studies). The population of class XI students of SMA Negeri 6 Pontianak, the sample was 30%. Data collection technique is an indirect communication technique data collection tool used in this study was a questionnaire. Based on the processing and analysis of the data that has been carried out, it can be concluded that there is an achievement motivation for grade XI students of SMA Negeri 6 Pontianak. This can be seen from the results of the study which states that students have enough responsibility, are oriented towards success, the need for feedback as well as innovative then have a pretty good achievement motivation. Keywords: Achievement Motivation